Long-read 16S rRNA amplicon sequencing reveals microbial characteristics in patients with colorectal adenomas and carcinoma lesions in Egypt - Asmaa A. El Leithy; Amira Salah El-Din Youssef; Auhood Nassar; Ramy K. Aziz; Nadin M. Khaled; Mina T. Mahrous; Ghobrial N. Farahat; Aya H. Mohamed; Yasser Mabrouk Bakr (Gut Pathogens)
Abstract Background Colorectal cancer (CRC) is among the five leading causes of cancer incidence and mortality. During the past decade, the role of the gut microbiota and its dysbiosis in colorectal tumorigenesis has been emphasized. Metagenomics and amplicon-based microbiome profiling provided insights into the potential role of microbial dysbiosis in the development of CRC. Aim To address the scarcity of information on differential microbiome composition of tumor tissue in comparison to adenomas and the lack of such data from Egyptian patients with CRC. Materials and methods Long-read nanopore sequencing of 16S rRNA amplicons was used to profile the colonic microbiota from fresh colonoscopic biopsy samples of Egyptian patients with CRC and patients with colonic polyps. Results Species richness of CRC lesions was significantly higher than that in colonic polyps (p-value = 0.0078), while evenness of the CRC group was significantly lower than the colonic polyps group (p-value = 0.0055). Both species richness and Shannon diversity index of the late onset CRC samples were significantly higher than those of the early onset ones. The Firmicutes-to-Bacteroidetes (F/B) ratio was significantly higher in the CRC group than in the colonic polyps group (p-value = 0.0054), and significantly higher in samples from early-onset CRC. The Enterococcus spp. were significantly overabundant in patients with rectal cancer and early-onset CRC, while Staphylococcus spp. were significantly higher in patients with sigmoid cancer and late-onset CRC. In addition, the relative abundance of Fusobacterium nucleatum was significantly higher in CRC patients. Conclusion Differentiating trends were identified at phylum, genus, and species levels, despite the inter-individual differences. In summary, this study addressed the microbial dysbiosis associated with CRC and colonic polyps groups, paving the way for a better understanding of the pathogenesis of early and late-onset CRC in Egyptian patients.